2014
DOI: 10.1002/app.41095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lignin removal on mechanical, thermal, and morphological properties of polylactide/starch/rice husk blend used in food packaging

Abstract: The aim of this work was to investigate the possibility of using cost‐effective natural filler in a biodegradable polymer and find new set of materials for green biocomposites to be used in food packaging. In this regard, rice husk (RH) and bleached rice husk (BRH) have been used in the form of powder and the effect of lignin removal on mechanical and thermal properties of prepared composites with poly(l‐lactide) and starch were studied. Using FTIR technique, the lignin removal from RH has been approved. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…After washing the supplied material with hot water, it was washed with distilled water at 25°C and finally dried in an oven for 48 h at 110°C. 25 The holocellulose and lignin content of all treated RSs including HWRS are obtained according to our previous study 9 and are reported in Table I.…”
Section: Rs Hot Water Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…After washing the supplied material with hot water, it was washed with distilled water at 25°C and finally dried in an oven for 48 h at 110°C. 25 The holocellulose and lignin content of all treated RSs including HWRS are obtained according to our previous study 9 and are reported in Table I.…”
Section: Rs Hot Water Treatmentmentioning
confidence: 99%
“…Therefore, it is required to be blended with other polymers, 8 specially poly(lactic acid) (PLA). 9 PLA is the most famous biodegradable polymer implementing starch as main part of structure. PLA is also a biodegradable polymer with a natural base that is synthesized from lactic acid and widely used in polymer industries for food packaging and medical applications.…”
mentioning
confidence: 99%
See 3 more Smart Citations